Domesticated water: four early neolithic wells in Moravia (cz) - Vostrovská, Ivana; Tichý, Radomír; Přichystal, Michal; Muigg, Bernhard; Urbanová, Kristýna; Kalábková, Pavlína (2021)
Abstract: Water wells are the most unique finds from the Early Neolithic period in Central Europe. These features provide unusual insight into societies and their settlements, as well as into the water management process. This article presents the updated results of material analyses and excavations of Early Neolithic wells at Mohelnice, Brno-Bohunice and Uničov in Moravia, Czech Republic. We studied the possibilities of the spatial and temporal distribution of wells on the example of these settlements. The social relation between the large longhouses and the wells in their immediate neighbourhood has not been proven. On the contrary, they could have been communal wells, serving the inhabitants of the entire settlement. Moreover, it turned out that in the Moravian region, geomorphological conditions were a key factor for choosing the location to build a well. By comparing radiocarbon dates, we estimated the time span of the existence of wells with respect to each other and to the settlements. Sealing and repairs of the well constructions prove that the first farmers maintained the wells over a long period of time. Studies of the well’s vertical sections shed light on its usage and decline; intentional backfilling of the well seems to have been common. Water management covered an entire cycle of activities, including the making of wooden buckets, which were mainly used for the pulling of water from wells